A comparative study of analytical and numerical models for the elastic behavior of composites reinforced by coated unidirectional fibers. (1st March 2023) - Böhm, Helmut J.
Abstract: A number of continuum mechanical models for the macroscopic and microscopic linear elastic behavior of composites reinforced by continuous, unidirectional, coaxially coated fibers are critically compared. For the study, the interphase is assumed to be of finite thickness and uniform. Selected analytical mean-field methods and Finite-Element-based periodic homogenization models are applied to obtaining predictions for the effective elastic tensors and moduli of generic composites of this type. In addition, the phase-averaged microscopic stresses are evaluated for some macroscopic load cases. By comparing these results modeling schemes capable of providing high-quality predictions are identified. Highlights: Systematic comparison of pertinent analytical and numerical micromechanical models "Construction kit" approach to two-step analytical models Very good agreement between periodic homogenization and some analytical models